The Relationship Between Jurisdiction and the Local Authority’s Online Sustainability Disclosure - Corina Joseph; Heidi Christy Mingi Michael (Universitas Trisakti, 2017)
The objective of this paper is to examine the relationship between jurisdiction and the extent of sustainability information disclosure on Malaysian local authority websites. The extent of online sustainability disclosure is examined utilizing the coercive isomorphism tenet in both quantitative and qualitative phases. In the quantitative stage, the analysis of 139 websites was conducted. The General Linear Model is utilized to determine the relationship between jurisdiction (measured by different states) and the extent of online sustainability information disclosure. In the qualitative phase, the semi-structured interviews were carried out to answer the underlying possible reasons derived from the quantitative phase. The quantitative phase provided evidence that various states have applied distinctive degree of coercive pressures on the extent of sustainability information disclosure on Malaysian local authority websites. The interview findings revealed additional factors that are relating to the jurisdiction: political, state leadership, and bureaucratic procedure implemented by different states. The paper has recognized the impact of coercive isomorphism for the jurisdiction utilizing both quantitative and qualitative phases.